Development and validation of a prediction model for persistent functional impairment among older ICU survivors. Issue 1 (5th October 2022) - Ferrante, Lauren E.; Murphy, Terrence E.; Leo‐Summers, Linda S.; O'Leary, John R.; Vander Wyk, Brent; Pisani, Margaret A.; Gill, Thomas M.
Abstract: Background: Critical illness often leads to persistent functional impairment among older Intensive Care Unit (ICU) survivors. Identification of high‐risk survivors prior to discharge from their ICU hospitalization can facilitate targeting for restorative interventions after discharge, potentially improving the likelihood of functional recovery. Our objective was to develop and validate a prediction model for persistent functional impairment among older adults in the year after an ICU hospitalization. Methods: The analytic sample included community‐living participants enrolled in the National Health and Aging Trends Study 2011 cohort who survived an ICU hospitalization through December 2017 and had a follow‐up interview within 1 year. Persistent functional impairment was defined as failure to recover to the pre‐ICU level of function within 12 months of discharge from an ICU hospitalization. We used Bayesian model averaging to identify the final predictors from a comprehensive set of 17 factors. Discrimination and calibration were assessed using area‐under‐the‐curve (AUC) and calibration plots. Results: The development cohort included 456 ICU admissions (2, 654, 685 survey‐weighted admissions) and the validation cohort included 227 ICU admissions (1, 350, 082 survey‐weighted admissions). In the development cohort, the median age was 81.0 years (interquartile range [IQR] 76.0, 86.0) and 231 (50.7%) participants were women; demographic characteristics were comparable in the validation cohort. The rates of persistent functional impairment were 49.3% (development) and 50.2% (validation). The final model included age, pre‐ICU disability, probable dementia, frailty, prior hospitalizations, vision impairment, depressive symptoms, and hospital length of stay. The model demonstrated good discrimination (AUC 71%, 95% confidence interval [CI] 0.66–0.76) and good calibration. When applied to the validation cohort, the model demonstrated comparable discrimination (AUC 72%, 95% CI 0.66–0.78) and good calibration. Conclusions: Application of the model prior to discharge from an ICU hospitalization may identify older adults at the highest risk of persistent functional impairment in the subsequent year, thereby facilitating targeted interventions and follow‐up.